Explorando a diversidade celular : guia ilustrado digital para o ensino de células e tecidos - Dias, Carolina Gonçalves (2024)
Cells possess great morphological and functional diversity, resulting in specialized cell types that form the histological tissues of the human body. The teaching and learning process regarding the contents involving cells and tissues have always been considered complex due to their microscopic nature, abstraction, structural deficiencies in public basic education schools, difficulty in finding suitable supporting material, and lack of detailed connections between specialized cells and tissues. For the reasons mentioned, this Master's Thesis aimed to construct a digital guide called "Exploring Cellular Diversity: A Knowledge and Activities Guide," as an educational product, in order to contribute to the integrated teaching of cellular and tissue biology in high school, targeted towards students and teachers. The Illustrated Digital Guide consists of 131 pages and is organized into sections that provide a review of cells, illustrations, and information on 14 specialized cell types along with activity suggestions. For each of the specialized cell types, the Guide presents the morphological and functional description, location in histological tissues, and interesting facts. The following specialized cells were addressed: neuron, red blood cell, adipocyte, myocyte, enterocyte, fibroblast, goblet cell, melanocyte, macrophage, lymphocyte, mast cell, osteoclast, spermatozoon, and oocyte. The Guide also includes a section with suggestions for 06 activities aimed at high school, placing the student as the protagonist of their learning process, incorporating investigative teaching, playfulness, and collaborative work as central elements. The educational product is an innovative production for the teaching of cells and tissues, combining original illustrations of specialized cells, descriptions, micrographs, and classroom activities